1991
DOI: 10.2115/fiber.47.6_263
|View full text |Cite
|
Sign up to set email alerts
|

The effect of air permeability and radiation property on free convective heat transfer of clothing system.

Abstract: Convective heat transfer coefficients of the vertical hot plate with the clothing material placed parallel to it, when there was no forced flow in surroundings, were measured. The effect of air penetration both through the permeable clothing material and through the bottom of air space was studied.The effect of radiation property of the clothing material was also examined. The effect of penetration on heat transfer through the material was smaller than those through the bottom of the space when there was no fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Results suggest thermal resistance of the fabric and air space differs according to the characteristics of the air gap. For example, gaps may be irregularly shaped, of varying thickness and/or distributed in varying ways throughout the assembly (Wilson, et al, 1999a;Wilson, et al, 2000), orientated horizontally or vertically (Fowle, 1933;Hollands, et al, 1976;Spencer-Smith, 1977), and/or open or closed to the ambient environment (Satsumoto, et al, 1991). Wilson, et al, (1999a) suggested convection in very large air space, over a critical thickness of horizontal air space, may reduce thermal resistance ('dry') per unit thickness of the air space.…”
Section: Thickness Orientation and Height Of Air Layersmentioning
confidence: 99%
See 2 more Smart Citations
“…Results suggest thermal resistance of the fabric and air space differs according to the characteristics of the air gap. For example, gaps may be irregularly shaped, of varying thickness and/or distributed in varying ways throughout the assembly (Wilson, et al, 1999a;Wilson, et al, 2000), orientated horizontally or vertically (Fowle, 1933;Hollands, et al, 1976;Spencer-Smith, 1977), and/or open or closed to the ambient environment (Satsumoto, et al, 1991). Wilson, et al, (1999a) suggested convection in very large air space, over a critical thickness of horizontal air space, may reduce thermal resistance ('dry') per unit thickness of the air space.…”
Section: Thickness Orientation and Height Of Air Layersmentioning
confidence: 99%
“…Altering the air permeability of inner fabric layers has been shown to affect the thermal resistance of fabrics wrapped around a cylindrical model exposed to wind (Fan, 1998;Fan and Keighley, 1989) (the magnitude of the effect was described as 'minimal'). Air permeability of fabrics and convection was also considered important in still air when vertical air spaces were Ͻ10 mm (Satsumoto, et al, 1991). Under these circumstances convection may occur in the air space because the heated air in the air space is of lower air pressure than that of the ambient environment.…”
Section: Variables Affecting Heat Loss During Air Movementmentioning
confidence: 99%
See 1 more Smart Citation